Tools for Screening Prospective Investors - UNCTAD (World Bank, Washington, DC, 2018)
This note supplements note 6: screening prospective investors. The investment screening process requires suitable tools for assisting government agencies in their work. This note provides examples of tools that government agencies can adapt to their national context and use to develop the technical capacity to screen and select investors.